Convergence of income between Asean-5 and China - Lee, Koon Po. (Universiti Malaysia Sarawak (UNIMAS), 2006)
It is said that the People’s Republic of China plays an important role as a trading partner of ASEAN. This study examines convergence of income (using real GDP growth) between ASEAN-5 countries (namely Indonesia, Malaysia, the Philippines, Singapore and Thailand) and the People’s Republic of China for a period of 41 years of annually data from 1960 to 2000. Four empirical methods are used in this research, namely correlation coefficient, the standard ADF test, the Johansen-Juselius Cointegration analysis to test the convergence hypothesis and the Granger Causality test. Empirical results show that there are mutual relationship and correlation of real GDP growth between ASEAN-5 and the People’s Republic of China in the long run. From the finding using the Granger causality method, it is found out that ASEAN-5 countries are diverting their investments to the People’s Republic of China.